The devils [large type] - Abercrombie, Joe (Thorndike Press, 2025)
Holy work sometimes requires unholy deeds. Brother Diaz has been summoned to the Sacred City, where he is certain a commendation and grand holy assignment awaits him. But his new flock is made up of unrepentant murderers, practitioners of ghastly magic, and outright monsters. The mission he is tasked with will require bloody measures from them all in order to achieve its righteous ends. Elves lurk at our borders and hunger for our flesh, while greedy princes care for nothing but their own ambitions and comfort. With a hellish journey before him, it's a good thing Brother Diaz has the devils on his side.